2017
DOI: 10.21608/ejss.2017.3474
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sources and Rates of Nitrogen Fertilizers on Forage Yield and Nitrate Accumulation for Sudangrass

Abstract: AFIelD experiment was carried out at the experimental Station Farm in Giza, Agricultural Research Center, egypt, during the two successive summer seasons of 2012 and 2013. The experiment was to study the effect of varying sources, rates of nitrogen fertilizers on fresh and dry forage yields of sudangrass, chemical constituents, nitrate and nitrite accumulation in plant using a split-plot design with three replicates . The main plots were assigned to nitrogen fertilizer sources (Ammonium nitrate NH4 NO3 and amm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Further, this study established that the number of leaves per plant increase with increasing nitrogen rates, with Sudan grass having more leaves than Buffel grass. This implies that nitrogen fertilizer treatment for both types of grass ensured more leaves for making foliage for animal feeds [14]. These results agree with those of Mrid et al [20] and Wang et al [47], who reported that photosynthetic activities, leaf chlorophyll content, and other leaf attributes of maize crops improve under nitrogen fertilization.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Further, this study established that the number of leaves per plant increase with increasing nitrogen rates, with Sudan grass having more leaves than Buffel grass. This implies that nitrogen fertilizer treatment for both types of grass ensured more leaves for making foliage for animal feeds [14]. These results agree with those of Mrid et al [20] and Wang et al [47], who reported that photosynthetic activities, leaf chlorophyll content, and other leaf attributes of maize crops improve under nitrogen fertilization.…”
Section: Discussionsupporting
confidence: 90%
“…Sudan grass produced more forage yield compared to Buffel grass, this is because of the greater tiller number and number of leaves produced by Sudan grass than Buffel grass [1,14]. Moreover, the higher forage yield observed in Sudan grass was also attributed to the fact that the dry matter in the shoot was more than that in Buffel, making Sudan grass a better feed for animals due to its higher quality [52,53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have evaluated the use of ammonium nitrate, in the fertilization of the pastoral ecosystem. It has already been published research with ammonium nitrate fertilization in pastures of Coastcross (Cynodon dactylon;SILVEIRA et al, 2007;PRIMAVESI et al, 2006), Pensacola (Paspalum notatum Flügge; SILVEIRA et al, 2015), Sudan grass (Sudanese Sorghum; ABO-ZEID et al, 2017), Tifton 85 (Cynodon spp. ;BORGES et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, animal production is suffering scarcity, due to the competition between the production of human food and animal feed. Thus, legumes forage crops can be grown in the newly reclaimed soil and irrigated by saline water [5]. Like most legumes species, forage cowpea (Vigna unguiculata cv.…”
Section: Introductionmentioning
confidence: 99%